Economic-productive analysis of a mixed cattle-bubaline model mixed model in the Northern region of Corrientes Province in Argentina - Pablo Maldonado-Vargas; Vanesa Guadalupe Mierke; Liliana Laura Pellerano; Guillermo Sebastián Grimaldi; Orlando Alberto Álvarez; Natalia Mercedes Vallejos; Margarita Rosa Itatí Romero; Francisco Daniel Romero; Alexis Sebastián Bandeo; Gonzalo Enrique Tuñón; José Luis Konrad (Revista Científica)
The production of buffaloes has been consistently growing in Argentina, with an increase in the number of animals and spread in 19 of the 23 provinces of the country, with an evident regional grouping. The Northeastern region of Argentina contains the provinces of Corrientes, Formosa, Chaco, Misiones, and Entre Rios, where 88.89% of the buffaloes, with Corrientes having the most significant numbers of animals and farmers. The study aimed to analyze a mixed cattle-bubaline model’s economic and productive results. Data from farms in the region was used as the analysis unit, gathering data from infrastructure, management practices, and market situations. Quantitative data (target stocking rate, female replacements) and qualitative data (descriptions) were obtained using a survey within an agreement between the provincial government and the University. A simulation model was run with the gathered data to describe and analyze the system. A method developed by INTA (National Institute of Agriculture and Technology) was used, with an Excel worksheet devel-oped by the technical team of the Chaco-Formosa Regional Centre and modified afterward at the Economic Department of the Experimental Agriculture Station of Colonia Benitez. The main economic and productive characteristics were obtained, which generated helpful information for designing the productive systems with buffaloes in subproductive areas and allowed for decision-making in the diverse business systems. Highlighting the main differences within the simulation model in terms of key performance indicators for buffaloes: weaning percentage (75 to 80%), female productive life (20 years), replacement percentage (10%), and age at first service (24 months). The cattle subsystem is consistent with the traditional breeding system of the region, whose main objective is the sale of calves and culled cows, while the buffalo subsystem is a complete cycle, which results in the sale of steers surplus of replacement females and culled animals. The mixed cattle-bubaline model is utilized within an area of 3,600 ha and 35% of buffaloes of the whole herd of animals. The meat production per ha was 53 kg, and the stock efficiency was 33%. A gross income of $55,565/ha, net income of $3,802/ha, and profitability was 5.1%. In contrast, the cattle activity yielded 48 kg/ha of meat and 23% stock efficiency, $5,473 gross income, and 3% profitability. Simulations and models were formulated to objectively compare and evaluate the economic and productive performance contributing to the different farming systems’ mixed revenue sources. This resulted in the emerging subtropical buffaloes’ pasture-based systems from the wetlands, such as those from the region, being improved. In the context of climate change, the global increase in droughts and floods and price volatility constitute a real challenge. To achieve and offer the market a critical mass of cattle and buffalo meat that can reliably demonstrate the production processes carried out, the origin and quality of the product should be achieved by selling meat with more information on current demands. In this way, it will be possible to participate more actively in the formation of prices, partially reversing the power of the current market, focusing on adding value and receiving a price premium for what has been done, generating extra income in buffalo production systems as a livestock activity.